Sociodemographic profile and pattern of opioid abuse among patients presenting to a de-addiction centre in tertiary care Hospital of Kashmir - Farhat, Samina (J Basic Clin Pharm, 2015)
BACKGROUND: The substances abuse has become one of the major public health problems of present society. Recently there has been an increase in the incidence of substance abuse including that of opioids throughout the world. The proper assessment of the current trends and pattern of opioid abuse can be helpful in more effective intervention of this menace. MATERIALS AND METHODS: To find out various socio-demographic variables and pattern of opioid abuse, a predevised questionnaire was administered to 200 opioid patients who presented to de-addiction center for treatment. RESULTS: Majority of the participants (75%) were of young age group (20–30 years) and the mean age of subjects was 27.6 years. More than half of participants (55%) were abusing the opioid substances for < 3 years followed by 30% of the abusers who were using the opioids for 4–6 years. Oral route was the most common route(35%)of substance administration followed by chasing(13%) and intravenous(11%) routes. Diverted pharmaceuticals emerged as one of the common substances of abuse, and peer pressure was found to be the main reason to start substance abuse. CONCLUSION: A comprehensive preventive program targeting young adults needs to be formulated and strict laws against sales of diverted pharmaceuticals to be implemented.